Dynamic regulation of CD28 conformation and signaling by charged lipids and ions - Yang, W; Pan, W; Chen, S; Trendel, N; Jiang, S; Xiao, F; Xue, M; Wu, W; Peng, Z; Li, X; Ji, H; Liu, X; et al. (Springer Nature, 2017)
CD28 provides an essential co-stimulatory signal for T cell activation and its function is critical in antitumor immunity. However, the molecular mechanism of CD28 transmembrane signaling remains elusive. Here, we find that CD28 conformation and signaling are regulated by two counteractive charged factors, i.e. acidic phospholipid and Ca2+ ion. NMR structure shows that acidic phospholipids can sequester CD28 signaling motifs within the membrane, thus limiting CD28 basal signaling. T-cell receptor (TCR) activation induces local [Ca2+] increase around CD28, and Ca2+ can use its charges to directly disrupt CD28-lipid interaction, which leads to CD28 opening and signaling. TCR, Ca2+ , and CD28 together form a dual positive feedback circuit to significantly amplify T cell signaling and therefore increase antigen sensitivity. This work unravels a new regulatory mechanism of CD28 signaling, contributing to the understanding of the dependence of the co-stimulation signaling on TCR signaling and the high sensitivity of T cells.